A230 INFORMATION NEEDS AND PREFERENCES REPORTED BY INDIVIDUALS UNDERGOING COLONOSCOPY: RESULTS FROM A LARGE REGIONAL SURVEY. (15th March 2019) - Lee, E; Shafer, L; Walker, J; Waldman, C; Michaud, V; Yang, C; Bernstein, C N; Park, J; Wittmeier, K; Restall, G; Singh, H
Abstract: Aims: To determine for patients undergoing colonoscopy their experiences, needs, and preferences for information and to assess predictors of willingness to go direct-to-colonoscopy and self-reported ability to follow bowel preparation instructions Methods: A self-administered survey was distributed to patients in 8 endoscopy facilities in Winnipeg when they attended an outpatient colonoscopy. The survey assessed the amount, type, helpfulness, and satisfaction with information provided before the procedure and inquired about other possible sources of information in the future. Results: Of the 1, 580 respondents, 61% reported receiving adequate information about the indication for their procedure, 53% for the benefits of a colonoscopy, 44% for the risks of the procedure and 40% for expected follow-up after the procedure. Although 90% indicated that it would be helpful or very helpful to receive information from their family physicians, only 25% indicated they had received an adequate amount from their family physician for the current colonoscopy. For follow-up of results, 75% of respondents would find a phone call from their family physician or the colonoscopy service helpful/very helpful and 90% an in person visit with their family physician. For future follow-up colonoscopy, 91% of respondents stated a reminder notice in the mail from a central endoscopy service would be helpful, while 29% indicated that an email reminder would be unhelpful or very unhelpful. For direct-to-colonoscopy, 70% indicated that receiving a phone call from a nurse would make them comfortable to proceed without meeting the endoscopy physician first. Predictors of ability to follow the bowel preparation instructions included finding the distributed information to be clear or very clear [(OR) 5.6 (3.4–9.2)] and satisfaction with the information received [OR 1.7 (1.0–2.0)]. Significant predictors of willingness to go direct-to-colonoscopy for the next colonoscopy included finding the distributed information to be clear or very clear [OR 1.9 (1.2–3.1)], satisfaction with the information received [OR 1.7 (1.0–2.0)], and visiting with the endoscopist prior to their current colonoscopy [OR 3.2 (2.0–5.0)]. Conclusions: Our survey suggests a need to enhance the information distributed to patients before the colonoscopy, particularly on the risks of the procedure and on potential follow-up procedures. There is also an unmet need to involve family physicians in informing patients on the reason for colonoscopy, the nature of the procedure, bowel preparation, and what information they would receive after the colonoscopy. The use of the direct to colonoscopy approach can be facilitated by enhanced pre-colonoscopy information and informational phone contact from nurses. Funding Agencies: